Porous inverse vulcanised polymers for mercury capture. Issue 31 (2nd March 2016) - Hasell, T.; Parker, D. J.; Jones, H. A.; McAllister, T.; Howdle, S. M.
Abstract : Supercritical carbon dioxide is used to generate macroporosity in an inverse vulcanised polymer, which shows excellent promise for enhanced mercury capture and filtration from water. Abstract : Supercritical carbon dioxide is used to generate macroporosity in an inverse vulcanised polymer, which shows excellent promise for enhanced mercury capture and filtration from water.